Impact of Altered Mineral Metabolism on Pathological Cardiac Remodeling in Elevated Fibroblast Growth Factor 23 - Leifheit-Nestler, Maren; Richter, Beatrice; Basaran, Melis; Nespor, Julia; Vogt, Isabel; Alesutan, Ioana; Voelkl, Jakob; Lang, Florian; Heineke, Joerg; Krick, Stefanie; Haffner, Dieter (Frontiers in Endocrinology, 2018)
Clinical and experimental studies indicate a possible link between high serum levels of fibroblast growth factor (FGF) 23, phosphate and parathyroid hormone (PTH), deficiency of active vitamin D (1,25D) and klotho with the development of pathological cardiac remodeling, i.e. left ventricular hypertrophy and myocardial fibrosis, but a causal link has not been established so far. Here, we investigated the cardiac phenotype in klotho hypomorphic (kl/kl) mice and Hyp mice, two mouse models of elevated FGF23 levels and klotho deficiency, but differing in parameters of mineral metabolism, by using histology, quantitative real-time PCR, immunoblot analysis, and serum and urine biochemistry. Additionally, the specific impact of calcium, phosphate, PTH, and 1,25D on hypertrophic growth of isolated neonatal rat cardiac myocytes was investigated in vitro. Kl/kl mice displayed high serum Fgf23 levels, increased relative heart weight, enhanced cross-sectional area of individual cardiac myocytes, activated cardiac Fgf23/Fgf receptor (Fgfr) 4/calcineurin/nuclear factor of activated T cell (NFAT) signaling, and induction of pro-hypertrophic NFAT target genes including Rcan1, βMHC, BNP, and ANP as compared to corresponding wild-type mice. Investigation of fibrosis-related molecules characteristic for pathological cardiac remodeling processes demonstrated ERK1/2 activation and enhanced expression of Tgfb1, collagen I, and Mmp2 in kl/kl mice than in wild-type mice. In contrast, despite significantly elevation of serum and cardiac Fgf23, and reduced renal klotho expression, Hyp mice showed no signs of pathological cardiac remodeling. Kl/kl mice showed enhanced serum calcium and phosphate levels, while Hyp mice showed unchanged serum calcium levels, lower serum phosphate and elevated serum iPTH concentrations compared to corresponding wild-type mice. In cultured cardiac myocytes, treatment with both, calcium or phosphate significantly up-regulated endogenous Fgf23 mRNA expression and stimulated hypertrophic cell growth and expression of pro-hypertrophic genes. The treatment with PTH induced hypertrophic cell growth only, and stimulation with 1,25D had no significant effects. In conclusion, our data indicate that Hyp mice, in contrast to kl/kl mice appear to be protected from pathological cardiac remodeling during conditions of high FGF23 levels and klotho deficiency, which may be due, at least in part, to differences in mineral metabolism alterations, i.e. hypophosphatemia and lack of hypercalcemia.